The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1103/physrevb.77.035421
|View full text |Cite
|
Sign up to set email alerts
|

Bundling effects on the intensities of second-order Raman modes in semiconducting single-walled carbon nanotubes

Abstract: The second-order Raman modes in the range of 380-650 cm −1 were investigated for individually dispersed and aggregated HiPco single-walled carbon nanotubes ͑SWNTs͒ using a 700-985 nm tunable laser source. For individually dispersed SWNTs, this Raman region displays relatively weak response from both intermediate frequency modes ͑IFMs͒ and the overtones of the radial breathing mode ͑RBM͒, with the latter dominating. In contrast, for aggregated SWNTs, the IFMs dominate and gain significant intensity relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
1
17
1
Order By: Relevance
“…Such perturbations affect properties of cross-polarized excitations because of their complete delocalization in the radial dimension. Indeed, recent experiments report that the optical signatures of cross-polarized excitations are more pronounced in bundles as compared with individual tubes (45).…”
Section: Resultsmentioning
confidence: 99%
“…Such perturbations affect properties of cross-polarized excitations because of their complete delocalization in the radial dimension. Indeed, recent experiments report that the optical signatures of cross-polarized excitations are more pronounced in bundles as compared with individual tubes (45).…”
Section: Resultsmentioning
confidence: 99%
“…However, a Kataura plot can be built with other Raman bands (most notably the G -band [26]). Experimental REMs have also been shown for intermediate frequency modes (IFMs) [27,28] and RBM overtones [29]. The D band REP has been investigated for polyfluorenesorted SWCNTs [30].…”
Section: Introductionmentioning
confidence: 97%
“…Peak #4 at 574 cm −1 can be assigned to a combination of three different symmetry modes, that is, the RBM (A 1 , 294 cm Previous Raman measurements on chirality-mixed SWCNT samples detected some IFMs in the 600-1100 cm −1 frequency range excited in the E 33 /E 44 region 26 as well as in the 370-480 cm −1 frequency range excited in the E 11 /E 22 region. 29,30 Fantini et al observed only two peaks associated with the oTO mode combined with acoustic phonon modes. 26 The so-called 'step-wise' dispersive behaviors were observed in these studies because the IFMs have a strong chirality-and diameter-dependence, which jumps when the excitation photon energy goes from one 2n + m family to another.…”
mentioning
confidence: 99%
“…In addition, the weaker IFM peaks at 623 cm −1 (Peak #5) and 1145 cm −1 (Peak #10) can also be the sum and difference, respectively, of the oTO mode and the sum of i) and ii) (three phonon combinations) although it is also likely that Peak #5 is the RBM overtone as previously observed in Raman. 30 Furthermore, there are two other IFM peaks, that is, Peaks #3 and #4. Peak #3 at 487 cm −1 can be assigned to a combinational mode between the RBM (294 cm −1 ) and the 2 nd E 1 mode (LAlike, 213 cm −1 ).…”
mentioning
confidence: 99%